PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN, GAYA KEPEMIMPINAN, BUDAYA ORGANISASI, KUALITAS SUMBERDAYA MANUSIA, DAN KEPUASAN KERJATERHADAP KINERJA APARAT PEMERINTAHDAERAH (Studi Empiris Pada SKPD Kabupaten Rokan Hulu) - Mulyani, Karlina; -, Desmiyawati; Kurnia, Pipin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to determine whether the effect of budget participation, leadership styles, organizational culture, human resources, and job satisfaction of the performance of local government officials. The type of data used is primary data using questionnaires data collection techniques. Questionnaires were distributed as many as 90 pieces and data back as many as 74 pieces. Data were analyzed by using test data quality, normality test, classical assumptions, as well as using multiple linear regression analysis, and coefficient of determination with the help of a software program SPSS version 20.00. The results showed that budget participation, leadership styles, organizational culture, and job satisfaction affect the performance of local government officials. While the quality of human resources does not affect the performance of local government officials, with a coefficient of determination 0.861 which shows the influence of the independent variables used in the model study on the performance of local government officials as the dependent variable was 86.1%. Meanwhile, 13.9% is influenced by other variables not included in this study.Keywords: Participation budgeting, leadership styles, organizational culture,human resources, and job satisfaction